Atomic and Molecular Layer Deposition of Hybrid Mo–Thiolate Thin Films with Enhanced Catalytic Activity. (23rd April 2018) - MacIsaac, Callisto; Schneider, Joel R.; Closser, Richard G.; Hellstern, Thomas R.; Bergsman, David S.; Park, Joonsuk; Liu, Yunzhi; Sinclair, Robert; Bent, Stacey F.
Abstract: A synthetic route toward hybrid MoS2 ‐based materials that combines the 2D bonding of MoS2 with 3D networking of aliphatic carbon chains is devised, leading to a film with enhanced electrocatalytic activity. The hybrid inorganic–organic thin films are synthesized by combining atomic layer deposition (ALD) with molecular layer deposition (MLD) using the precursors molybdenum hexacarbonyl and 1, 2‐ethanedithiol and characterized by in situ Fourier transform infrared spectroscopy, and the resultant material properties are probed by X‐ray photoelectron spectroscopy, Raman spectroscopy, and grazing incidence X‐ray diffraction. The process exhibits a growth rate of 1.3 Å per cycle, with an ALD/MLD temperature window of 155–175 °C. The hybrid films are moderately stable for about a week in ambient conditions, smooth (σRMS ≈ 5 Å for films 60 Å thick) and uniform, with densities ranging from 2.2–2.5 g cm −3 . The material is both optically transparent and catalytically active for the hydrogen evolution reaction (HER), with an overpotential (294 mV at −10 mA cm −2 ) superior to that of planar MoS2 . The enhancement in catalytic activity is attributed to the incorporation of organic chains into MoS2, which induces a morphological change during electrochemical testing that increases surface area and yields high activity HER catalysts without the need for deliberate nanostructuring. Abstract : A new 3D MoS2 ‐like material is synthesized and applied to the hydrogen evolution reaction (HER), produced via atomic layer deposition/molecular layer deposition. The high HER activity of this [SCH2 CH2 S]2 Mo material results from the film restructuring in situ during electrochemical testing, increasing surface area.